Planlet Study of Kappaphycus Alvarezii Maumere Variety with ‎Different Colours from Tissue Culture Propagation at Seameo ‎Biotrop Bogor - Gloria Ika Satriani; Rukisah Rukisah (ISEJ : Indonesian Science Education Journal, 2026)
Tissue culture propagation of Kappaphycus alvarezii Maumere variety at SEAMEO BIOTROP Bogor produced planlets exhibiting an unusual color shift from the original brown (LC) to green (LH) at a mutation ratio of 1:50 within culture bottles. This study aimed to characterize the molecular identity and genetic relationships of these color-variant planlets using the Internal Transcribed Spacer (ITS) DNA barcoding marker and phylogenetic reconstruction in MEGA X. DNA sequencing using ITS primers revealed that both color variants (LH and LC) confirmed as K. alvarezii based on NCBI BLAST analysis (Query Cover: 92%; Percent Identity: 87.52%; Accession No. JN673973.1). The nucleotide compositions showed T(U): 23.84%, C: 22.48%, A: 25.48%, G: 28.20% (LH) and T(U): 25.28%, C: 26.40%, A: 25.42%, G: 22.89% (LC), with total nucleotide lengths of 734 and 712 bp, respectively. No single nucleotide polymorphism (SNP) was associated with the color characteristic detected between the two variants. Genetic distance analysis indicated a close relationship between LH and LC (distance: 0.155), while both showed considerable divergence from the reference K. alvarezii KC905270.1 (0.626 and 0.629, respectively) and from Eucheuma isiforme (0.565 and 0.563). The phylogenetic tree confirmed that LH and LC belong to the same species with a distinct color phenotype potentially attributable to epigenetic or physiological factors. These findings provide molecular baseline data for the utilization of tissue-culture-derived K. alvarezii Maumere variety in seaweed aquaculture programs in Indonesia.